Enhanced intragranular precipitation strengthening in Sc-microalloyed ultrafine-grained SiCp/Al-Cu-Mg composites via retrogression and re-ageing heat treatment - Yunpeng Cai; Kan Liu; Yiwei Dong; Andong Hua; Yishi Su; Qiubao Ouyang; Di Zhang (Materials & Design)
Ultrafine-grained Al matrix composites suffer from the insufficient dislocation accumulation capability and intragranular precipitation strengthening due to their length-scale dependent precipitation behaviors. In this work, a combination of Sc-microalloying and a retrogression and re-ageing (RRA) route was applied on the SiCp/Al-Cu-Mg composites to achieve well-balanced strength and ductility. Compared to the T6 treatment, RRA heat treatment exhibit a significant strengthening effect in Sc-microalloyed composites with only a slight loss in ductility. The yield strength and ultimate strength of the Sc-RRA samples reach up to 686.4 MPa and 734.5 MPa, respectively. The plastic deformation mechanism was analyzed by thermal activation analysis and TEM observation of deformed microstructure. The plastic deformation of UFG composites, both with and without Sc, is primarily governed by a dislocation-grain boundary interaction mechanism. As confirmed by the observed stacking faults, the Sc-microalloyed composite subjected to T6 treatment suffers from poor dislocation storge capacity and insufficient intragranular precipitation strengthening. In contrast, the RRA treatment promotes the formation of intragranular Al3Sc precipitates and GP zones, which improve the dislocation accumulation capability and precipitation strengthening of ultrafine-grained composites by pinning dislocations. This work provides an accessible pathway to exploit aluminum matrix composites with advanced strength-ductility balance.